ChemInform Abstract: Broensted‐Acid‐Mediated Divergent Reactions of Betti Bases with Indoles: An Approach to Chromeno[2, 3‐b]indoles Through Intramolecular Dehydrogenative C2‐Alkoxylation of Indole. Issue 48 (10th November 2016) - Deb, Mohit L.; Pegu, Choitanya Dev; Deka, Bhaskar; Dutta, Prantu; Kotmale, Amol S.; Baruah, Pranjal K.
Abstract: Under Broensted acid catalysis, naphthol‐based Betti bases either couple with indoles or undergo a new type of C—C bond cleavage giving diarylmethanes (not shown).